Modelling the cost-effectiveness of tofacitinib for the treatment of rheumatoid arthritis in the United States. (2nd November 2018) - Claxton, Lindsay; Taylor, Matthew; Gerber, Robert A.; Gruben, David; Moynagh, Dermot; Singh, Amitabh; Wallenstein, Gene V.
Abstract: Background and objectives: Rheumatoid arthritis (RA) is a chronic, debilitating disease affecting an estimated 1.5 million patients in the US. The condition is associated with a substantial health and economic burden. An economic model was developed to evaluate the cost-effectiveness of tofacitinib (a novel oral Janus kinase inhibitor) versus biologic therapies commonly prescribed in the US for the treatment of RA. Methods: A cost–utility model was developed whereby sequences of treatments were evaluated. Response to treatment was modeled by HAQ change, and informed by a network meta-analysis. Mortality, resource use and quality of life were captured in the model using published regression analyses based on HAQ score. Treatment discontinuation was linked to response to treatment and to adverse events. Patients were modeled as having had an inadequate response to methotrexate (MTX-IR), or to a first biologic therapy (TNFi-IR). Results: The tofacitinib strategy was associated with cost savings compared with alternative treatment sequences across all modeled scenarios (i.e. in both the MTX-IR and TNFi-IR scenarios), with lifetime cost savings per patient ranging from $65, 205 to $93, 959 (2015 costs). Cost savings arose due to improved functioning and the resulting savings in healthcare expenditure, and lower drug and administration costs. The tofacitinib strategies all resulted in an increase in quality-adjusted life years (QALYs), with additional QALYs per patient ranging from 0.01 to 0.22. Conclusions: Tofacitinib as a second-line therapy following methotrexate failure and as a third-line therapy following a biologic failure produces lower costs and improved quality of life compared with the current pathway of care.